Observational Study of Pediatric Inpatient Pain, Nausea/Vomiting and Anxiety - Michael Schlegelmilch; Salima Punja; Hsing Jou; Andrew S. Mackie; Jennifer Conway; Bev Wilson; Maria Spavor; Dawn Hartfield; Sunita Vohra (MDPI AG, 2019)
Background: The prevalence and severity of pain, nausea/vomiting, and anxiety (PNVA) among hospitalized children is not well established. We describe the prevalence and severity of PNVA among hospitalized patients from oncology, general pediatrics, and cardiology services in a tertiary care center. Methods: Patients were recruited on admission and enrolled if their caregiver consented, spoke English, and were anticipated to stay 2−30 days. Symptoms were measured weekdays using age-validated tools. PNVA symptoms were described and compared. Results: We enrolled 496 (49.4%) patients of 1005 admitted. Patients were predominantly Caucasian (57.9%) on their first admission (53.6%). The average (SD) age was 8.6 years (5.9) in oncology, 4.2 (5.3) in general pediatrics and 2.6 (4.0) in cardiology. 325 (65.6%) patients reported anxiety, 275 (55.4%) reported nausea and 256 (52.0%) reported pain. Mean (SD) severity out of 10 was 3.7 (2.5) for anxiety, 3.2 (2.1) for nausea and 3.0 (1.5) for pain. Prevalence of PNVA was no different between clinical programs, but pain (p = 0.008) and nausea (p = 0.006) severity were. PNVA symptom co-occurrence was positively correlated (p < 0.001). Conclusions: Anxiety was the most common and severe symptom for hospitalized children. Patients in oncology demonstrated the least severe pain and nausea with no difference in anxiety between services.